What's in a Name? A Coordinated Approach toward the Correct Use of a Uniform Nomenclature to Improve Patient Reports and Databases. Issue 6 (14th March 2016) - Tack, Véronique; Deans, Zandra C.; Wolstenholme, Nicola; Patton, Simon; Dequeker, Elisabeth M. C.
ABSTRACT: The Human Genome Variation Society (HGVS) recommendations provide standardized nomenclature for reporting variants. This should be encouraged in molecular pathology—both for issuing diagnostic reports and for correct data recording in electronic databases. Many providers of external quality assessment (EQA) promote the correct use of HGVS nomenclature by scoring variant descriptions used in EQA reports. This study focuses on the type and impact of variant nomenclature errors. An assessment was made of EGFR gene variant nomenclature by four EQA providers (European Society of Pathology [ESP], European Molecular Genetics Quality Network [EMQN], United Kingdom National External Quality Assessment Service for Molecular Genetics, and the French national Gen&Tiss EQA scheme) for two EQA distributions. Laboratories testing for oncology biomarkers make different errors when describing EGFR gene variants. Significant differences were observed regarding inclusion of the correct reference sequence: EMQN participants made fewer errors compared to ESP EQA participants ( P ‐value = 0.015). The analysis of ESP EQA participants showed significant improvement over 2 years ( P ‐value = 0.016). Results demonstrate the need for improvement of variant reporting according to HGVS guidelines. Consequences of using incorrect mutation nomenclature are currently perceived as low by many laboratories, but the impact will rise with an increased reliance on databases to assist in result analysis.